The Influence of Radioiodine Therapy on the Number of Circulating Epithelial Cells (CEC) in Patients with Differentiated Thyroid Carcinoma – a Pilot Study - Winkens, T.; Pachmann, K.; Freesmeyer, M. (Experimental and Clinical Endocrinology & Diabetes, 2014)
The aim of this pilot study was to investigate the changes of circulating epithelial cells in the blood of patients with differentiated thyroid cancer after radioiodine-therapy with I-131.The cells were detected by fluorescence-microscopy via the epithelial-cell-adhesion-molecule (EpCAM), a molecule described to be over-expressed in most carcinoma tissues and also present on circulating cells deriving from primary site. Epithelial cells were assessed before radioiodine-therapy, as well as 2 days, 14 days, and 3 months after therapy. 2 patient groups were examined: 1) patients with thyroid cancer receiving a first radioiodine-therapy after thyroidectomy (RITfirst, n=13), and 2) patients with thyroid cancer in need of repeated radioiodine-therapy due to local or metastatic recurrences (RITrep, n=15). Circulating epithelial cell changes were correlated to changes of serum-thyroglobulin and to clinical response evaluated 3 months after therapy.Patients with an early decrease of cells after radioiodine-therapy (RITfirst 7/13; RITrep 2/15) showed an increase of serum-thyroglobulin in most of the cases (RITfirst 5/7; RITrep 2/2). In the RITrep group, a decrease in cell counts 2 days after radioiodine-therapy indicated a clinical response in 90% of the cases.This study indicates that the number of circulating epithelial cells in differentiated thyroid cancer undergo changes in response to radioiodine-therapy. The destruction of cells through radioiodine-therapy may induce a short-term release of thyroglobulin in the blood. A clear relationship between the clinical outcome and the cell changes could not be found, but early cell decreases may help identifying patients more likely to respond to radioiodine-therapy.
Keywords: circulating tumor cells; CTC; thyroid cancer; tumor marker